Workload Analysis of Pharmacists at Tanjung Selamat General Hospital, Langkat, 2025 - Nemas Adelina Lubis; Rahmad Gurusinga; Chandra Pranata (JURNAL KESMAS DAN GIZI (JKG), 2026)
Pharmaceutical personnel play a crucial role in ensuring the quality of healthcare services in hospitals. A high workload, if not properly managed, can negatively affect performance, patient safety, and service quality. This study aims to analyze the workload of pharmacists at the Pharmacy Installation of Tanjung Selamat General Hospital, Langkat, focusing on four main variables: the type and number of tasks, limitations in human resources, duration and work shift patterns, and work adjustment strategies.This study employed a qualitative approach using a descriptive method. Data were collected through in-depth interviews with one key informant (Head of the Pharmacy Installation) and three triangulation informants (Pharmaceutical Technical Personnel and Pharmacy Assistants). Data analysis was conducted through data reduction, data presentation, and conclusion drawing.The results indicate that pharmacists and pharmaceutical personnel at Tanjung Selamat General Hospital handle various types of tasks, including administrative and non-clinical duties such as medical waste management. The limited number of staff leads to task overlap, uneven shift distribution, and an increased risk of work fatigue. The 24-hour shift system has not been optimally implemented due to the disproportionate distribution of personnel. Work adjustment strategies, such as task prioritization and teamwork, have been applied; however, they remain individual-based and are not yet supported by a structured managerial system.In conclusion, the workload of pharmaceutical personnel is considered high and complex. The hospital needs to increase staffing levels, evaluate the shift system, and strengthen supporting systems such as standard operating procedures (SOPs) and information technology. Adjustments in human resource management policies are essential to maintain work efficiency and the quality of pharmaceutical services